High‐Throughput Tag‐Sequencing Analysis of Early Events Induced by Ochratoxin A in HepG‐2 Cells. Issue 1 (17th September 2015) - Zhang, Yu; Qi, Xiaozhe; Zheng, Juanjuan; Luo, YunBo; Huang, Kunlun; Xu, Wentao
ABSTRACT: Ochratoxin A (OTA) is produced by fungi of the species Aspergillus and Penicillium . OTA has displayed hepatotoxicity in mammals. Although recent studies have indicated that OTA influences liver function, little is known regarding its impact on differential early liver toxicity. In this study, we report high‐throughput tag‐sequencing (Tag‐seq) analysis of the transcriptome using Solexa Analyzer platform after 4 h of OTA treatment on HepG‐2 cells. The analyses of differentially expressed genes revealed the substantial changes. A total of 21, 449 genes were identified and quantified, with 2726 displaying significantly altered expression levels. Expression level data were then integrated with a network of gene–gene interactions, and biological pathways to obtain a systems‐level view of changes in the transcriptome that occur with OTA resistance. Our data suggest that OTA exposure leads to an imbalance in zinc finger expression and shed light on splicing factor and mitochondrial‐based mechanisms.